Estrés prenatal por SARS-CoV-2 como factor de riesgo de la esquizofrenia: Prenatal SARS-CoV-2 stress as a risk factor for schizophrenia - Falla-Castillo, Mariana Lucía (2022)
Schizophrenia is a serious mental disorder characterized by delirium and hallucinations (positive symptoms), as well as abulia, depression and cognitive impairment (negative symptoms), which entails a large socioeconomic burden requiring early diagnosis and timely treatment. This disease has a multifactorial origin, being the prenatal stress caused by viral infections one of its possible factors; this due to, it could harm neuronal development. This research aims to review the knowledge on prenatal SARS-CoV-2 infection as a risk factor in the development of schizophrenia. The proper development of the nervous system requires an anti-inflammatory state of the maternal immune system during the second trimester of pregnancy. In this period, viral infection processes, such as Covid-19, act as proinflammatory stimuli that alter the molecular environment and induce "maternal immune activation" (MAI), an event associated with the functional alteration of dopaminergic neurons that generates imbalances in dopamine concentration. Likewise, MAI affects the phagocytic activity of microglia, triggering excessive synaptic pruning; in addition, it induces epigenetic changes in them, which added to their survival of up to 20 years, would lead to the long-term development of schizophrenia.